Suppression of Immunoglobulin G Synthesis as a Result of Antibody-Mediated Suppression of Immunoglobulin M Synthesis in Chickens - Kincade, Paul W. (1970)
Development of heterogeneity of immunoglobulin classes has been investigated in the chicken by studying the effects of antibody-mediated suppression of IgM synthesis. Treatment of 13-day embryos with purified goat antibodies to IgM resulted in the elimination of IgM-containing cells from the bursa of Fabricius of 16- and 19-day embryos. When combined with bursectomy at hatching, administration of anti-IgM in ovo suppressed the synthesis not only of IgM but also of IgG. A number of experimental birds lacked detectable circulating immunoglobulins, plasma cells, and germinal centers when killed at 10 weeks of age. Contrasting results were obtained when IgM synthesis was suppressed after bursectomy at hatching. Birds so treated produced little or no IgM but synthesized normal amounts of IgG. The results suggest that, within the bursal environment, IgG-producing cells arise exclusively from cells that previously synthesized IgM. A model for generation of antibody variability is presented.